Studying the Co-production of AI Implementation in National Public Libraries - Mergel, Ines (Springer, 2025)
AI implementation in National Libraries is a multi-actor endeavour that includes many internal as well as external contributors. The literature on the subject is, however, sparse and still developing. In this chapter, I provide the theoretical framework and the research design for the EU LibrarIN project that is built on the co-production literature in the public management field. The resulting theoretical framework of digital co-production has guided the case study selection and inquiry and set the foundation for the empirical data analysis of the 12 case studies on AI implementation in National Libraries.
Keywords: Artificial Intelligence; AI; Co-production; National Libraries; Digital transformation; Stakeholder engagement; fi=Julkisjohtaminen|en=Public Management|